2013
DOI: 10.1149/2.016305jss
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization Study by Transmission Electron Microscopy of SrTiO3Thin Films Prepared by Plasma-Assisted ALD

Abstract: The crystallization behavior of thin strontium titanate (SrTiO3, STO) films with ∼15 nm thickness was studied by Transmission Electron Microscopy (TEM). Amorphous STO films with [Sr]/([Sr]+[Ti]) ratio ranging from 0.50 to 0.63 were deposited at 350°C by plasma-assisted ALD and subsequently treated by rapid thermal annealing in flowing N2 for crystallization. Different temperatures and annealing durations were employed to fully characterize the crystallization process. TEM analysis showed that transrotational c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
17
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 25 publications
9
17
0
1
Order By: Relevance
“…The cracks seem less pronounced for the Sr-rich films. This is consistent with the previous TEM study 34 which revealed an increased nucleation density leading to a higher density of smaller grains for the Sr-rich films as compared with the stoichiometric STO films. The Ti-rich STO films showed altogether a different surface morphology.…”
Section: B Thin Film Microstructure and Morphologysupporting
confidence: 93%
See 3 more Smart Citations
“…The cracks seem less pronounced for the Sr-rich films. This is consistent with the previous TEM study 34 which revealed an increased nucleation density leading to a higher density of smaller grains for the Sr-rich films as compared with the stoichiometric STO films. The Ti-rich STO films showed altogether a different surface morphology.…”
Section: B Thin Film Microstructure and Morphologysupporting
confidence: 93%
“…3(c) and 3(f)). Referring to previous crystallization studies, 34 the morphological differences were explained by a locally incomplete crystallization process. In particular, additional AFM analyses (see Fig.…”
Section: B Thin Film Microstructure and Morphologymentioning
confidence: 68%
See 2 more Smart Citations
“…Furthermore, in the VIS range, the refractive indices of nanocrystalline STO films are found to be 2.36 and 2.31 (@550 nm) for as-deposited and annealed films, respectively. Its value decreased with annealing, however, the observed values is larger than the reported amorphous (1.83-2.06) and polycrystalline (2.05-2.12) films [28,[32][33][34]. It should be noted that the film thickness which is generally lower than 100 nm has affects film properties, however, according to our best knowledge there is no comparative information on the effect of film thickness on thin STO films.…”
Section: Optical Propertiesmentioning
confidence: 60%